Discerning wisdom : the sapiential literature of the Dead Sea scrolls - Goff, Matthew J. (Supplements to Vetus Testamentum,, 2007)
Before the discovery of the Dead Sea Scrolls, Ben Sira was the only Hebrew wisdom text from the late Second Temple period. The Qumran scrolls provide an abundance of previously unknown Hebrew sapiential material. Discerning Wisdom provides a systematic overview of all the Qumran texts that are commonly identified as wisdom compositions. This literature raises issues such as the incorporation of apocalypticism and Torah piety into the sapiential tradition. The Dead Sea Scrolls offer crucial evidence for understanding the wisdom of the late Second Temple period and the reception of traditional wisdom in Early Judaism.